Évaluation du développement territorial comme processus d'innovation et d'institutionnalisation : le cas du Territoire du Alto Sertão do Piauí e Pernambuco au Nordeste du Brésil - Jean-Philippe Tonneau; Marc Piraux; Emilie Coudel; Sergio Guilherme de Azevedo (VertigO)
Because of their transversal and multipurpose character, evaluation of territorial development policies cannot rely on the tools used to assess sectoral policies. Procedural issues are mainly dominant, since arrangements essentially focus on governance and coordination. In order to evaluate a procedural approach, specifying the assessment referential is necessary. What and how evaluate ? It is the purpose of this paper, which aims to contribute to assessment methods, by analysing the impacts of a research-action to develop a "weakened" territory of the "Alto Sertão of Piaui and Pernambuco ", located in Northeast of Brazil. The objective is to characterize the processes at work, in order to understand them and to define their scope. The first part lists the expectations regarding the territorial development policies: increasing and mobilizing the human, social and institutional capitals, so as to develop adaptation and innovation capacities and improve systems of activities and governance. Territorial engineering processes must be assessed in the light of their ability to build competencies, to encourage innovation and have it recognized by the governance systems. The methods used to evaluate the experiment are then presented both qualitative and quantitative.The experiment is described in the second part of the article. Actors’s training and project elaboration were combined trough the organization of a governance forum, technical experiments and training sessions.  In terms of governance, this led to the creation of a local consortium as well as a technical agency, both in charge of implementing different development actions, within a territorial project. Our goal is to give some facts on the action and its impacts. The third part discusses the insight brought by this experiment. The authors notice the ideal conditions of the experiment, and how difficult its replication turned out to be. They evaluate how the learning process contributed to the development of human, social and institutional capitals, mobilized in terms of collective skills, them alone being able to change situations by creating new development opportunities, by achieving innovation trough the construction of pragmatic rules, offering a solution to the studied issues.The conclusion analyse the evaluation criteria and the possible improvements to the methodologies developped.